Method for rapidly detecting contents of potassium, sodium and zinc elements in iron-containing material
Patent Information
- Application Number
- CN202511912246.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-17
- Publication Date
- 2026-03-17
AI Technical Summary
[0003]目前没有快速测定各种含铁料中钾、钠、锌元素含量的标准分析方法,参考公开的中国专利CN113533307A一种高炉除尘灰中钙、镁、铜、铝、锰、钛、钾、钠、铅、锌元素含量的测定方法可知,通过高温灼烧除去试样中的碳、硫,再利用微波消解试样,采用电感耦合等离子体原子发射光谱法可以同时对钙、镁、铜、铝、锰、钛、钾、钠、铅、锌等进行测定
1)预建立一套同时满足烧结矿和除尘灰中K2O、Na2O、Zn等有害元素含量快速检测需求的方法,研究出一套系列校准溶液即可同时适用于烧结矿和除尘灰的成分测定,含量覆盖范围大,适用于工厂大批量试样的检测,缩短检测分析时间、提高工作效率;
Smart Images

Figure CN121678640A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of testing and analysis technology, and in particular to a method for rapidly detecting the content of potassium, sodium and zinc elements in iron-containing materials. Background Technology
[0002] Zinc, potassium, and sodium have a significant impact on the smooth operation of blast furnace smelting. High zinc content can damage the blast furnace lining, furnace shell, and gas treatment system. Zinc deposition in the refractory brick lining causes volume expansion, generating internal stress and leading to material damage. Potassium, sodium, and zinc are harmful elements in blast furnace feedstock; excessive content negatively affects blast furnace output and lifespan. Potassium and sodium deteriorate the metallurgical properties of coke, affecting the reducibility, pulverization rate, and softening properties of sintered ore, causing pellet expansion, which is detrimental to blast furnace smelting. The fundamental measure to prevent zinc, potassium, and sodium hazards in blast furnace smelting is to reduce the content of raw materials and fuels fed into the furnace. Therefore, accurately testing the zinc, potassium, and sodium content in the blast furnace feedstock is of great significance.
[0003] Currently, there is no standard analytical method for rapidly determining the content of potassium, sodium, and zinc in various iron-containing materials. Referring to the published Chinese patent CN113533307A, "A Method for Determining the Content of Calcium, Magnesium, Copper, Aluminum, Manganese, Titanium, Potassium, Sodium, Lead, and Zinc in Blast Furnace Dust," it is known that carbon and sulfur in the sample are removed by high-temperature calcination, and then the sample is digested by microwave. Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-AES) can be used to simultaneously determine the content of calcium, magnesium, copper, aluminum, manganese, titanium, potassium, sodium, lead, and zinc.
[0004] Subsequently, experiments were conducted to establish a rapid testing method for the zinc, potassium, and sodium content in the iron-containing feed material of blast furnaces. This method provides timely and accurate test results for production, thereby reducing the use of reagents and labor, lowering instrument operating costs, improving testing efficiency, reducing analysis costs, and providing fast and powerful data support for scientific research and production. Summary of the Invention
[0005] This invention provides a method for rapidly detecting the potassium, sodium, and zinc content in iron-containing materials. This method enables rapid detection, meets production needs in terms of testing cycle, and provides accurate results that meet national standards for similar materials.
[0006] To achieve the above objectives, the present invention employs the following technical solution: A method for rapidly detecting the potassium, sodium, and zinc content in iron-containing materials includes the following steps: S1. Preparation of reagents; S2. Sample weighing; S3. Sample pretreatment; S4. Conduct matrix matching experiment: Weigh 0.3000g of high-purity iron, place it in a 100mL polytetrafluoroethylene (PTFE) beaker, moisten it with water, add 15-20mL of hydrochloric acid, 3-5mL of hydrofluoric acid, and 4-6mL of perchloric acid, cover with a PTFE lid, place it on a hot plate and heat it at 140-160℃. S5. Plotting ICP curves: Using 1 mg / mL potassium, sodium, and zinc standard solutions, transfer the corresponding volumes of standard solutions into the iron matrix stock solution, then shake well and dilute to 100 mL in a volumetric flask. Plot the ICP curves based on the relationship between the strength and content of the potassium, sodium, and zinc standard solutions. S6. Using an ICP instrument to measure samples: After preparing the calibration solution, measure the calibration solution in order of increasing concentration, starting with the blank calibration solution. Take 3 readings for each measurement and average the result. After measuring the calibration solution, measure the standard sample solution first, and then measure the sample solution. If the test solution exceeds the calibration curve range, dilute the test solution or re-prepare the calibration solution. S7. Test results: The test results for sintered ore are the values indicated by the ICP instrument, and the test results for dust collector ash, blast furnace ash, and electric field ash are 5 times the values indicated by the instrument.
[0007] Furthermore, the reagents include: high-purity iron with a purity > 99.99%, hydrochloric acid with a density of 1.18–1.19 g / mL, hydrofluoric acid with a density of 1.15–1.18 g / mL, perchloric acid with a density of 1.68–1.76 g / mL, hydrochloric acid 1+1 solution, and standard solutions of potassium, sodium, and zinc, each with a mass concentration of 1 mg / mL.
[0008] Furthermore, the specific sample weighing includes: weighing 0.4990 to 0.5010 g of pre-dried sample, accurate to 0.0002 g; weighing 0.0990 to 0.1010 g of dust collector ash, blast furnace ash, and electric field ash samples, accurate to 0.0002 g; placing them in a porcelain crucible; and placing the porcelain crucible in a high-temperature furnace at 800℃ to 850℃ for 30 to 40 minutes until the carbon in the sample is completely removed.
[0009] Furthermore, the sample pretreatment specifically includes: placing the sample in a 100mL dry and clean PTFE beaker, adding 15-20mL of hydrochloric acid and 3-5mL of hydrofluoric acid, heating it on a hot plate, with an asbestos board placed under the PTFE beaker; after the sample dissolves, adding 4-6mL of perchloric acid, heating until fumes are produced to about 1-2mL, removing it and cooling it slightly, adding 8-12mL of hydrochloric acid, heating to dissolve the salts, removing it and cooling it to room temperature, transferring it to a 100mL plastic volumetric flask, diluting it to the mark with water and mixing well.
[0010] Furthermore, the operating conditions of the ICP instrument are as follows: RF power 1100–1200W, auxiliary gas flow rate 0.4–0.6L / min, nebulizer gas flow rate 0.5–0.7L / min, vertical observation, observation height 11.5–12.5mm, rinsing pump speed 90–110r / min, analysis pump speed 45–55r / min, pump stabilization time 4–6s, sample rinsing time 25–35s, long-wave exposure time 4–6s, and short-wave exposure time 13–17s; the selected analytical wavelengths for potassium, sodium, and zinc in ICP are: K: 769.896nm, Na: 589.592nm, and Zn: 206.200nm and 213.856nm, while simultaneously satisfying a correlation coefficient of 0.999 or higher for the corresponding calibration curves of potassium, sodium, and zinc.
[0011] Furthermore, during the ICP working curve plotting process, the calibration curve is prepared as follows: the volume of the standard solution for K element is 0-20 ml, the mass fraction of K element is 0-4%, and the mass fraction of K2O is 0-4.8184%; the volume of the standard solution for Na element is 0-10 ml, the mass fraction of Na element is 0-2%, and the mass fraction of Na2O is 0-2.696%; the volume of the standard solution for Zn element is 0-20 ml, and the mass fraction of Zn element is 0-4%.
[0012] Furthermore, the iron-containing material includes sintered ore, dust collector ash, and electric furnace ash containing 0.01% to 5.00% potassium oxide, 0.01% to 3.00% sodium oxide, and 0.01% to 4.00% zinc.
[0013] Compared with the prior art, the beneficial effects of the present invention are: 1) Establish a method that can simultaneously meet the requirements for rapid detection of harmful elements such as K2O, Na2O, and Zn in sintered ore and dust removal ash. Develop a series of calibration solutions that can be applied to the composition determination of both sintered ore and dust removal ash, with a wide content coverage, suitable for the detection of large batches of samples in factories, shortening the detection and analysis time and improving work efficiency. 2) Optimize the sample dissolution method and shorten the dissolution time from 70 hours to 2 hours to ensure timely data reporting; 3) The application of inductively coupled plasma atomic emission spectrometry reduces a significant amount of internal control standard setting work in the absence of corresponding national standard materials. Compared with X-ray fluorescence spectrometry, the method establishment process is relatively simple. Attached Figure Description
[0014] Figure 1 This is a schematic diagram of the K-element ICP working curve described in this invention.
[0015] Figure 2 This is a schematic diagram of the Na element ICP working curve described in this invention.
[0016] Figure 3 This is a schematic diagram of the ICP working curve of the Zn element described in this invention.
[0017] Figure 4 This is a schematic diagram of the ICP working curve of the Zn element described in this invention. Detailed Implementation
[0018] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings: This invention discloses a method for rapidly detecting the potassium, sodium, and zinc content in iron-containing materials, comprising the following steps: S1. Prepare reagents and materials; High-purity iron, purity > 99.99%; Hydrochloric acid, ρ approximately 1.19 g / mL; Hydrofluoric acid, p approximately 1.15 g / mL, analytical grade; Perchloric acid, ρ approximately 1.68 g / mL; Hydrochloric acid, 1+1 solution, that is, concentrated hydrochloric acid to water in a volume ratio of 1:1; Purchase certified standard solutions of potassium, sodium, and zinc, each with a mass concentration of 1 mg / mL. PTFE beaker, 100mL; Plastic volumetric flask, 100mL; high temperature furnace; Inductively coupled plasma atomic emission spectrometers should be equipped with high-salt and hydrofluoric acid resistant atomizers and corresponding atomization chambers.
[0019] S2. Sample weighing; Weigh 0.5000g of the pre-dried sample, accurate to 0.0002g. Weigh 0.1000g of the dust collector ash, blast furnace ash, and electric field ash samples, accurate to 0.0002g. Place them in a porcelain crucible and calcine the crucible in a high-temperature furnace at 800℃~850℃ for 30 minutes until the carbon in the sample is completely removed.
[0020] S3. Sample pretreatment; Place the sample in a 100mL dry and clean PTFE beaker, add 15mL hydrochloric acid and 4mL hydrofluoric acid, place it on a hot plate and heat it. An asbestos board should be placed under the PTFE beaker. After the sample dissolves, add 5mL perchloric acid and heat until fumes are produced to about 2mL. Remove it and let it cool slightly, then add 10mL hydrochloric acid and heat to dissolve the salts. Remove it and cool it to room temperature. Transfer it to a 100mL plastic volumetric flask, dilute it with water to the mark and mix well.
[0021] S4. Determine the optimal operating conditions for the ICP instrument: Table 1 Table 2 The correlation coefficient of the calibration curve for each element must reach 0.999 or higher; The final selected analytical wavelengths for potassium, sodium, and zinc in ICP were: K 769.896nm, Na 589.592nm, Zn 206.200nm, and Zn 213.856nm.
[0022] S5. Matrix matching test; To ensure that the matrix of the calibration solution is as consistent as possible with the matrix in the test solution, high-purity iron that matches the sample is added as a matrix, as shown in Table 3; Table 3 The total iron content of sintered ore is about 55% to 58%, calculated based on the iron content of 60% in the sintered ore sample; however, the iron content in the dust sample is generally between 10% and 50%, with a large fluctuation range; as can be seen from the above experimental data, the determination results of K2O, Na2O and Zn are basically unchanged under different iron contents, so the matrix matching can be the same as that of the sintered ore sample. Weigh 0.3000g of high-purity iron and place it in a 100mL PTFE beaker. Wet the beaker with water and add 15mL of hydrochloric acid, 4mL of hydrofluoric acid, and 5mL of perchloric acid. All acids are of analytical grade. Cover the beaker with the PTFE lid and heat it on a hot plate at a temperature of about 150℃ until it is completely dissolved. Open the lid and evaporate it to dryness. Add 10mL of hydrochloric acid (1+1) and dissolve it on the hot plate. Cool the beaker.
[0023] S6. Plot the ICP working curve; Using 1 mg / mL potassium, sodium, and zinc standard solutions, transfer the corresponding volumes of standard solutions into the iron matrix stock solution, then shake well and dilute to 100 mL in a volumetric flask for PTFE. The table below shows the method for preparing calibration curves; Table 4 The plotted curve is shown below. Figure 1-4 The correlation coefficients of the working curves for potassium, sodium, and zinc elements in the iron-containing material shown in the figure all reach above 0.9995.
[0024] S7. Use an ICP instrument to measure the sample; After preparing the series of calibration solutions, measure the solutions in order from low to high concentration, starting with the blank calibration solution. Take three readings for each measurement and average the result. After measuring the calibration solutions, first measure the standard sample solution (iron ore), then measure the sample solution. If the test solution is outside the range of the calibration curve, the test solution can be diluted or the calibration solution can be reconstituted. The selection of spectral lines should be based on the presence of background interference. A blank solution or reagent with added iron can be used for the experiment.
[0025] S8. Test results; The test results for sintered ore are the values indicated by the ICP instrument, while the test results for dust collector ash, blast furnace ash, and electric field ash are five times the values indicated by the instrument.
[0026] Iron ore standard materials were used as samples for routine quality control to confirm the feasibility of the working curve and the stability of the equipment. Samples were only tested after each quality control result was within the allowable tolerance, and the results of two analyses should not exceed the allowable tolerance specified in the table below: Table 5 Precision test: The results of 11 sample analyses are shown in Table 6, and the relative standard deviation (RSD, n=11) is 0.731 to 1.025%.
[0027] Table 6 After using this method, the accuracy-standard substance validation is shown in Table 7; Table 7 Accuracy – Spike recovery test results are shown in Table 8; Table 8 The spiked recovery test results were 95.60–104.90%, which meets the relevant provisions of GB / T 27417-2017 "Guideline for Conformity Assessment and Validation of Chemical Analysis Methods". This proves that the detection method described in this invention is accurate, reliable, and efficient, and fully meets the detection requirements for potassium, sodium, and zinc content in the iron-containing material.
[0028] The following embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operation processes. However, the scope of protection of the present invention is not limited to the following embodiments. Unless otherwise specified, the methods used in the following embodiments are conventional methods.
[0029] Example S1. Weigh 0.5000g of sintered ore sample, place it in a porcelain crucible, and put the porcelain crucible into a high-temperature furnace at 800℃~850℃ for 30 minutes until the carbon in the sample is completely removed.
[0030] S2. Place the sample in a 100mL dry and clean PTFE beaker, add 15mL hydrochloric acid and 4mL hydrofluoric acid, and heat on a hot plate. After the sample dissolves, add 5mL perchloric acid, heat until fumes appear (about 2mL), remove and let cool slightly, add 10mL hydrochloric acid, heat to dissolve the salts, remove and cool to room temperature, transfer to a 100mL plastic volumetric flask, dilute with water to the mark and mix well.
[0031] S3. Determine the optimal operating conditions for the ICP instrument: Table 9 S4. Select the analysis wavelengths for potassium, sodium, and zinc in ICP: K 769.896nm, Na 589.592nm, Zn 206.200nm.
[0032] S5. Plot the calibration curve: Dilute the calibration solution with 1 mg / mL potassium, sodium and zinc standard solutions to obtain the calibration solution. To ensure that the matrix of the calibration solution is as consistent as possible with the matrix in the test solution, add high-purity iron that matches the sample as the matrix. Table 10 shows the concentration of the calibration curve.
[0033] Table 10: Calibration Curve Concentration S6. After preparing the series of standard solutions, measure the standard solutions in order from low concentration to high concentration, starting with the blank standard solution. Take three readings for each measurement and take the average value. After measuring the standard solutions, first measure the standard sample sinter (wkd88306d-2017). The results are K2O: 0.118%, Na2O: 0.103%, Zn: 1.034%, which meets the allowable difference range of GB / T6730.76. Then measure the sample solution.
[0034] S7. The test results for sintered ore are K2O 0.0932%, Na2O 0.0184%, and Zn 0.0226%, which are the instrument readings.
Claims
1. A method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials, characterized in that, It comprises the following steps: S1, preparing reagent; S2, sample weighing; S3, sample pretreatment; S4, carrying out matrix matching experiment: weighing 0.3000g high-purity iron, placing it in a 100mL PTFE beaker, wetting it with water, adding 15-20mL hydrochloric acid, 3-5mL hydrofluoric acid, and 4-6mL perchloric acid, covering it with a PTFE cover, and placing it on an electric heating plate to heat, with the temperature controlled at 140-160℃; S5, drawing ICP working curve: using 1mg / mL potassium, sodium, and zinc standard solutions, respectively taking corresponding volumes of the standard solutions into the iron matrix mother liquor, shaking them well, and then diluting them to 100mL in a volumetric flask, and drawing the ICP working curve according to the relationship between the strength and content of the potassium, sodium, and zinc standard solutions; S6, using ICP instrument to determine sample: after the calibration solution is prepared, the calibration solution is determined in the order of concentration from low to high, starting from the blank calibration solution, reading 3 times each time, taking the average value, and then determining the standard sample solution and the sample solution; If the test solution exceeds the calibration curve range, dilute the test solution, or reconfigure the calibration solution; S7, test result; The sinter test result is the ICP instrument detection value, and the dust ash, blast furnace ash, and electric field ash test results are 5 times the instrument value.
2. The method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials according to claim 1, characterized in that, The reagent comprises: high-purity iron with a purity of >99.99%, hydrochloric acid with a density of 1.18-1.19g / mL, hydrofluoric acid with a density of 1.15-1.18g / mL, perchloric acid with a density of 1.68-1.76g / mL, 1+1 hydrochloric acid solution, and potassium, sodium, and zinc standard solutions with a mass concentration of 1mg / mL.
3. The method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials according to claim 1, characterized in that, The sample weighing specifically comprises: Weighing 0.4990-0.5010g of pre-dried sample, with an accuracy of 0.0002g, and weighing 0.0990-0.1010g of dust ash, blast furnace ash, and electric field ash sample, with an accuracy of 0.0002g, and placing them in a porcelain crucible, and placing the porcelain crucible in a high-temperature furnace at 800-850℃ for 30-40min to completely remove the carbon in the sample.
4. The method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials according to claim 1, characterized in that, The sample pretreatment specifically comprises: placing the sample in a 100mL dry and clean PTFE beaker, adding 15-20mL hydrochloric acid and 3-5mL hydrofluoric acid, and placing it on an electric heating plate, with an asbestos plate under the PTFE beaker; after the sample is dissolved, adding 4-6mL perchloric acid, heating to smoke about 1-2mL, taking it off and cooling it, adding 8-12mL hydrochloric acid, heating to dissolve the salts, taking it off and cooling it to room temperature, and then transferring it into a 100mL plastic volumetric flask, diluting it to the mark with water, and mixing it well.
5. The method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials according to claim 1, characterized in that, The ICP instrument has the working conditions of RF power 1100-1200 W, auxiliary gas flow 0.4-0.6 L / min, atomizer gas flow 0.5-0.7 L / min, vertical observation, observation height 11.5-12.5 mm, flushing pump speed 90-110 r / min, analysis pump speed 45-55 r / min, pump stabilization time 4-6 s, sample flushing time 25-35 s, long-wave exposure time 4-6 s, and short-wave exposure time 13-17 s; the analysis wavelengths of K, Na and Zn in the ICP are K: 769.896 nm, Na: 589.592 nm and Zn: 206.200, 213.856 nm, and the correlation coefficients of the calibration curves corresponding to K, Na and Zn are all above 0.
999.
6. The method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials according to claim 1, characterized in that, In the process of drawing the ICP working curve, the calibration curve is prepared as follows: the volume of the standard solution of K element is 0-20 ml, the mass fraction of K element is 0-4%, and the mass fraction of K2O is 0-4.8184%; the volume of the standard solution of Na element is 0-10 ml, the mass fraction of Na element is 0-2%, and the mass fraction of Na2O is 0-2.696%; and the volume of the standard solution of Zn element is 0-20 ml, and the mass fraction of Zn element is 0-4%.
7. The method for rapidly detecting the content of potassium, sodium and zinc in iron-containing materials according to claim 1, characterized in that, The iron-containing material includes sinter, dust and electric furnace dust containing potassium oxide 0.01%-5.00%, sodium oxide 0.01%-3.00% and zinc 0.01%-4.00%.
Citation Information
Patent Citations
Method for measuring contents of calcium, magnesium, copper, aluminum, manganese, titanium, potassium, sodium, lead and zinc elements in blast furnace fly ash
CN113533307A